Control of the Private Life and Crime Prevention in Serbia - Stepanović, Ivana (Zbornik Instituta za kriminološka i sociološka istraživanja, 2015)
Governmental Control of private life is a controversial topic in the world today, and the key problem is the conflict between security and the right to privacy. The right to privacy is a basic human right and an important pillar of democracy, and the control of the private sphere is necessary for maintaining security. While creating a balance between the two conflicting interests seems to be inevitable in order to resolve current problems in the sphere of law and policymaking, we must also raise a question about what the public opinion in Serbia is regarding governmental control of private life. The question of public opinion on mass surveillance was raised in America and Europe after Edward Snowden's revelations in 2013, and it is necessary to raise it in Serbia too, especially considering the heritage of socialist Yugoslavia. It is important to question the role of governmental control over the private lives of citizens in crime prevention, and investigate to what extent citizens themselves are willing to sacrifice the right to privacy for more security. The aim of this paper is to analyse the phenomenon of controlling private life in the function of preventing crime and violence in Serbia.